Pengaruh Perputaran Kas, Total Asset Turnover, Debt To Equity Ratio, dan Current Ratio Terhadap Return on Asset Pada Perusahaan yang Terdaftar di Indeks LQ45 - Bayu Wulandari; Irwanto Irwanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
To be able to maintain survival, companies must have the ability to generate profits. This research purpose is to examine whether cash turnover, total asset turnover, debt to equity ratio, and current ratio have an effect on return on asset. The population in this study are companies listed in index LQ45. The sampling method used in this study was purposive sampling and obtained as many as 26 samples. The research method used in this research is descriptive analysis and multiple linear regression analysis. The result showed that in partial cash turnover has no effect and significant on return on asset, total asset turnover has effect and not significant on return on asset, debt to equity ratio has no effect and not significant on return on asset, and current ratio has no effect and significant on return on asset. Simultaneously cash turnover, total asset turnover, debt to equity ratio, and current ratio together has effect and not significant on return on asset. Keywords: Cash Turnover, Total Asset Turnover, Debt to Equity Ratio, Current Ratio, and Return on Asset